Parental bonding and neuropsychological performance are associated with episodic simulation of future events in trauma‐exposed patients with major depressive disorder. Issue 7 (8th May 2016) - Parlar, Melissa; Lee, Alex; Haqqee, Zeeshan; Rhooms, Latisha; Lanius, Ruth A.; McKinnon, Margaret C.
Abstract: Introduction: Major depressive disorder (MDD) and trauma‐related disorders are associated with deficits in remembering the past and imagining the future (i.e., episodic simulation). We examined parental bonding and neuropsychological performance in relation to episodic simulation in trauma‐exposed patients with recurrent MDD. Methods: Trauma‐exposed patients with MDD ( n = 21) and matched controls ( n = 20) completed a future‐oriented Autobiographical Interview, the Parental Bonding Instrument, and a standardized neuropsychological battery. Results: Patients with major depressive disorder generated fewer episodic details for future neutral events compared to controls. Although higher reported levels of maternal care were associated with increased specificity of negative future events among the patient group, higher maternal overprotection was related to decreased specificity of negative and positive future events. Higher levels of performance on measures of intelligence, verbal memory, executive functioning, and sustained attention were associated with increased specificity of future events. Conclusions: Maternal relations during childhood and neuropsychological performance are related to the specificity of episodic simulation in adult patients with MDD. Childhood experience continues to influence memory performance into adulthood. Abstract : This study examined episodic simulation of future events in relation to parental bonding and neuropsychological performance in trauma‐exposed participants with major depressive disorder. Higher reported levels of maternal care and higher levels of performance on neuropsychological measures were related to increased specificity of future events.